دور مصرف سورية المركزي في الرقابة على المصارف الأخرى وآلية تفعيله - الرضا عقبة; غنام ريم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تحتلّ الصناعة المصرفية أهمية كبيرة في الحياة الاقتصادية والاجتماعية، نظراً لكون القطاع المصرفي العنصر الرئيس في توطيد الثقة بسياسة الدولة ورعايتها للمصالح الاقتصادية، وهذا يقتضي العمل على إيجاد قطاع مصرفي قوي يساعد على إمداد القطاعات المختلفة بالتمويل اللازم لمباشرة نشاطها وتقديم الخدمات المصرفية على اختلاف أنواعها، ومن الضروري إخضاع هذا القطاع لعملية الرقابة التي تقع مسؤوليتها بشكل رئيس على عاتق المصرف المركزي، وذلك للحفاظ على سلامة المراكز المالية للمصارف، والتوصل إلى قطاع مصرفي سليم، يحافظ على حقوق المودعين والمستثمرين، ويضمن سلامة تنفيذ السياسة النقدية للدولة بالشكل المناسب، للمساهمة بشكل فعّال في تطور الاقتصاد الوطني وازدهاره. وسنتناول في هذا البحث مفهوم الرقابة المصرفية وتعريفها وأهميتها وبشكل خاص رقابة المصرف المركزي وما هي مبادئ الرقابة المصرفية الفعّالة من وجهة نظر لجنة بازل للرقابة المصرفية، كذلك سوف نتعرف على آلية عمل مديرية مفوضية الحكومة لدى المصارف التي يمارس مصرف سورية المركزي رقابته على المصارف الأخرى من خلالها. وقد تم التوصل إلى مجموعة من النتائج و التوصيات والتي كان أهمها: ضرورة التزام مصرف سورية المركزي بمبادئ بازل للرقابة المصرفية الفعّالة بشكل كامل. إيجاد مجموعة من القوانين والتشريعات تمكِّن مصرف سورية المركزي من ممارسة دوره الرقابي بشكل فعّال، وتساعد على تطبيق مبادئ بازل. إلزام المصارف المتخصصة على تطبيق مبادئ إدارة المخاطر الائتمانية. ضرورة زيادة عدد المراقبين لدى المصرف المركزي ليتمكّنوا من القيام بالرقابة على مختلف الفروع المصرفية. Banking industry occupies a great importance in the economic and social life، because the banking sector is the main element in establishing confidence in the state policy and its protection of economic interests. This demands work on finding a strong banking sector، which helps on supplying necessary financing to the different sectors to start their activities، and offering bank services with all its different kinds. It is necessary to make this sector subject to a supervision process، whose responsibility is the task of the Central Bank mainly. It would be so in order to keep up the safety of financial centers for the banks، to reach a healthy banking sector which maintains the rights of investors and depositors and guarantees the safety in executing the critical policy of the state appropriately in order to contribute effectively in developing the national economic and its prosperity. We shall illustrate in this research the concept of banking supervision، its definition and importance especially the supervision of Central Bank as well as the rules of effective banking supervision from Bazel committee’s view for banking supervision. We will also recognize the work mechanism of government management at the banks which enables the Central Syrian Bank to supervise other banks through them. The paper has obtained a group of results and recommendations. The most important are: The necessity of Central Syrian Bank to keep the principles of Bazels’ for effective banking supervision completely. Finding a group of laws and legislations which enables the Central Bank of Syria to practice its supervisory role effectively and helps to apply Bazel’s principles. The obligation of the specialized banks in applying the principles for managing the fiduciary risks. The necessity for increasing the supervisors in the Central Bank to be able to practice supervision on the different banking branches.